Ukhūwah Islāmiyyah sebagai Pilar Moderasi Beragama dan Solidaritas Sosial di Era Modern - Hamzah Saputra; Rosmini; Sohrah (Aksioreligia, 2025)
The phenomena of social fragmentation, religious polarization, and the decline of humanitarian solidarity highlight the importance of reviving the value of ukhuwah (brotherhood) in Islam. This study aims to examine the concept of ukhuwah in the Qur’an, particularly in Surah Al-Ḥujurāt verse 10, and its relevance to modern social life. The research employs a library research method with a thematic interpretation approach (tafsir mawḍū‘ī). Primary data sources include the Qur’an and both classical and contemporary exegeses such as Tafsir Al-Marāghī, Tafsir Al-Mishbah, and Tafsir Al-Azhar. The data were analyzed descriptively and qualitatively by interpreting the verse in its social and humanitarian context. The results indicate that ukhuwah consists of four main levels: ukhuwah ‘ubūdiyyah (brotherhood among all of God’s creations), ukhuwah insāniyyah (human brotherhood), ukhuwah wathaniyyah (national brotherhood), and ukhuwah dīniyyah (religious brotherhood). Surah Al-Ḥujurāt [49]:10 emphasizes that true ukhuwah is realized through peace (iṣlāḥ) and piety. These values are relevant in strengthening unity among Muslims, promoting interreligious tolerance, and fostering social solidarity in contemporary society.